On immunoglobulin heavy chain gene switching: two gamma 2b genes are rearranged via switch sequences in MPC-11 cells but only one is expressed. - Lang, R B (1982)
During B lymphocytes differentiation, switches in the expression of heavy chain immunoglobulin constant region (CH) genes occur by a novel DNA recombination mechanism. We have investigated the requirements of the CH gene switch by characterizing two rearranged gamma 2b genes from a gamma 2b producing mouse myeloma (MPC-11). One of the two gamma 2b genes is present in 2-3 copies per cell (gamma 2b strong hybridizer) while the other is present in approximately 1 copy per cell (gamma 2b weak hybridizer). Genomic clones of the gamma 2b strongly hybridizing gene indicate that this is an abortive switch event between the S gamma 3 and S gamma 2b regions. However, clones of the gamma 2b weakly hybridizing gene suggest a functional rearrangement due to the presence of VH, JH and S mu sequences. The switch-recombination sites of these rearranged gamma 2b genes and those of other CH genes show a high degree of preference for the sequence AGGTTG 5' of either the S mu donor site or the appropriate CH S acceptor site. AGGTTG and its analogs are rare in the S mu region, are somewhat prevalent in s alpha and in the case of S mu are found 5' of a tandemly repeated DNA sequence (GAGCT, GGGGT) comprising most of S mu.